“Weakness of the Soul:” The Special Education Tradition at the Intersection of Eugenic Discourses, Race Hygiene and Education Policies - Wagner, Josefine (Conatus - Journal of Philosophy, 2019)
According to Vera Moser, the first professorship of healing pedagogy, Heilpädagogik at the University of Zürich in 1931, established pedagogy of the disabled as an academic discipline. Through the definition of the smallest common denominator for all disabilities, which Heinrich Hanselmann called “weakness of the soul,” a connecting element of “imbecility, deaf-mutism, blindness, neglect and idiocy” was established. Under Nazi rule, school pedagogy advanced to völkisch, nationalist special pedagogy, shifting from the category of “innate imbecility” to a broader concept of disability. As an outcome of these programs and policies, 300,000 people with disabilities were killed as a part of the “T4 Aktion.” Within just a few decades after World War II, special pedagogy expanded its sphere of influence through professionalization and institutionalization in West and East Germany and across Europe. This paper explores how special pedagogy aligned itself with the Nazi regime’s discourse and policy on eugenics and race hygiene, leading to the murder and mass sterilization of “disabled” children and adults. It probes questions regarding the extent to which the professionalization of special pedagogy has drawn from the Nazi-era terminology of the deficient and foreign to legitimate the contemporary migrant bias in German and Austrian special pedagogical care.